2019
DOI: 10.1016/j.radi.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Professional protectionism; a barrier to employing a sonographer graduate?

Abstract: Introduction: The national sonographer workforce deficit is not a new challenge and has been driven by the increasing demand for ultrasound services. The current educational models only facilitate small trainee numbers and are unable to keep abreast of the demand for trained sonographers. This is partially due to the intensive (and often one to one) sonographer training which has instigated much debate relating to alternative models of education. Alongside this, debate continues on the educational level of any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Recent studies have suggested that a culture of protectionism and motivation to maintain high demand for sonographer services exist within the field of sonography. 7,8 Notwithstanding, the need for more support from management is seen as an important factor in sonographer training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that a culture of protectionism and motivation to maintain high demand for sonographer services exist within the field of sonography. 7,8 Notwithstanding, the need for more support from management is seen as an important factor in sonographer training.…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell and Nightingale 7 argue that the disparity between the number of sonographers and the high demand for their services has placed this population in a position of power. Moreover, they suggest that sonographers are motivated to maintain this imbalance, which is thought to explain a present heavy resistance to change 7,8 . Sevens and Reeves 8 in the United Kingdom, hypothesised strong leadership on a national level is currently lacking and will be a crucial factor in overcoming this issue.…”
Section: Introductionmentioning
confidence: 99%
“…In the sonography group there was a clear sense that the lack of regulation and dedicated professional body was related to the perceived lack of recognition and professional identity. 25,26 Interestingly, however participants in the therapeutic group who do have a regulatory and professional body, also recounted this lack of recognition and professional identity.…”
Section: (Tr)mentioning
confidence: 99%
“…it's about professionalism, you know, you've got to change (DR) These findings are not surprising in periods of rapid change (for example, the apprenticeship developments) and professional protectionism becomes evident as resistance to change. 25,26 In particular, for sonography, the introduction of a degree apprenticeship route will align to a complete career restructure. 29 However, also within the sonography group, participants reported seeing opportunities for alternative educational models and training which aligned to the professional pride sub category.…”
Section: (Dr)mentioning
confidence: 99%
“…We would like to congratulate Mitchell, Nightingale and Reeves for their article on 'Competence to capability: An integrated career framework for sonographers' for providing a suggested framework for skills escalation for sonographers 1 . This is particularly relevant to the current work being undertaken by Health Education England (HEE) to attempt to address the sonographer shortages in England 2 and challenges faced by the introduction of a wider range of entry points to ultrasound practice 3,4 .…”
Section: Dear Editormentioning
confidence: 99%